Prognostic value of the pre-treatment albumin-to-alkaline phosphatase ratio in patients with lower-grade glioma: a propensity score matching study - Huang, Xiaoming; Li, Lingjuan; Zang, Di (Frontiers in Pharmacology, 2025)
Introduction:The albumin-to-alkaline phosphatase ratio (AAPR) has recently emerged as a novel prognostic biomarker in various solid tumors. However, its clinical value in lower-grade glioma (LGG) remains unclear.Methods:We performed propensity score matching (PSM) to balance baseline characteristics between groups. Restricted cubic spline (RCS) analysis was used to evaluate the nonlinear relationship between AAPR and survival outcomes. Survival differences were assessed using Kaplan–Meier analysis, and both univariate and multivariate Cox regression models were applied to identify independent prognostic factors. Finally, a predictive nomogram was developed to estimate 1-, 3-, and 5-year overall survival.Results:RCS analysis revealed a nonlinear relationship between AAPR and OS (p = 0.0349). Patients were stratified by the median AAPR value (0.704), and those in the AAPR-High group (≥0.704) had significantly better OS (log-rank p = 0.0042) and progression-free survival (PFS) (log-rank p = 0.042) than those in the AAPR-Low group. AAPR showed stronger prognostic value in low-risk subgroups. Higher AAPR was significantly associated with better OS in univariate (p = 0.005, HR = 0.541, 95% CI: 0.353–0.829) and multivariate Cox analyses (p = 0.046, HR = 0.630, 95% CI: 0.400–0.993). The AAPR-based nomogram demonstrated good predictive performance for 1-, 3-, and 5-year OS, validated in the PSM cohort.Discussion:Pre-treatment AAPR is a simple, non-invasive, and effective biomarker for predicting prognosis in LGG patients, particularly those at lower clinical risk.